2008
DOI: 10.1167/8.4.26
|View full text |Cite
|
Sign up to set email alerts
|

Equivalence of physical and perceived speed in binocular rivalry

Abstract: The relative dominance of gratings engaged in binocular rivalry can be influenced by their surroundings. One striking example occurs when surrounding motion is congruent with one but not the other grating (C. L. Paffen, S. F. te Pas, R. Kanai, M. J. van der Smagt, & F. A. Verstraten, 2004). However, such center-surround stimulus configurations can also modulate perceived speed, via a directionally tuned process (H. P. Norman, J. F. Norman, J. T. Todd, & D. T. Lindsey, 1996). We recorded rivalry for Gabor patch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 63 publications
1
18
0
Order By: Relevance
“…When stimuli are defined by spatial form but also have a temporal component, rivalry is usually possible provided the temporal frequencies are similar (42,43). Over a limited range, faster stimuli will dominate over slow or static stimuli (44)(45)(46)(47). However, this is by no means a general property; for some dichoptic motion combinations, faster stimuli are less dominant (46).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When stimuli are defined by spatial form but also have a temporal component, rivalry is usually possible provided the temporal frequencies are similar (42,43). Over a limited range, faster stimuli will dominate over slow or static stimuli (44)(45)(46)(47). However, this is by no means a general property; for some dichoptic motion combinations, faster stimuli are less dominant (46).…”
Section: Discussionmentioning
confidence: 99%
“…Other image properties can play a major role in binocular rivalry. Contextual information in many domains, including color (54,55), global motion (56), surround orientation (55,57,58), surround motion (47,59), percept history (60), and depth information (61), can also influence the pattern of dominance during rivalry in a variety of ways. Furthermore, it has been demonstrated that coherent visual objects, such as houses or faces, produce deeper rivalry suppression with more global (and fewer piecemeal) alternations, compared with simple grating stimuli (34).…”
Section: Discussionmentioning
confidence: 99%
“…The data shown in Figure 1 are replotted fromBaker&Graf Figure3therein) and illustrate the phenomena and stimuli used. Baker & Graf (2008). Perceived speed was measured using a speed matching task, for a range of surround directions, and is shown for three observers (symbols) and their average (line).…”
mentioning
confidence: 99%
“…Perceived speed was measured using a speed matching task, for a range of surround directions, and is shown for three observers (symbols) and their average (line). Methodological details are given in Baker &Graf(2008).Notethatourstudyusedacentral grating stimulus surrounded by a noise texture (see inset), whereas most previous studies had used dot motion. The physical speed of both centre and surround was always 0.5deg/sec (dashedline).…”
mentioning
confidence: 99%
“…Although airplanes capture land from a bird's eye perspective as well as maps, they are more readable for children than maps, especially because it is a real representation of the landscape, while map depicts individual elements using different symbols [7]. With increasing age, the ability to find and identify objects and stimuli worsens [8,9], reaction time increases [10,11]; perception of space, orientation and navigation deteriorates [12].…”
Section: Introductionmentioning
confidence: 99%